Isolation, Identification and Antagonistic Activity of Marine Actinomycetes Isolated From the Muthupet Mangrove Environment - Sathiyaseelan, K (International Journal of Pharmaceutical & Biological Archive, 2011)
Actinomycetes are the representative of terrestrial microorganisms and usually are isolated from soils. When compared to terrestrial actinomycetes, however, a small portion of work has been conducted on marine actinomycetes. The marine Actinomycetes were well known for its antagonistic activity. In the present study, the sediment samples were collected from different stations of the Muthupet mangrove ecosystem , situated along the Southeast coast of India, for isolation of actinomycetes, using Kuster agar medium. The isolated strains were identified using physiological and biochemical methods. Seven Actinomycetes sp were isolated and tested for their antagonistic activity against human pathogens like, Escherichia coli, Pseudomonas sp., Klebsiella sp. and Bacillus sp.